On the Magma Chambers beneath Klyuchevskoi Volcano, Kamchatka - Khubunaya S.A.; Gontovaya L.I.; Sobolev A.V.; Khubunaya V.S. (2018)
AAbstract—Numerous summit and parasitic eruptions of moderate potassium magnesian and high-alumina basalts and basaltic andesites, their mineralogic and geochemical features, and the composition of in situ chilled melt inclusions in the olivine of cinder lapilli discharged by Klyuchevskoi Volcano all provide evidence of the presence of magma chambers beneath the volcano. This is also supported by a dualism in the variation of CaO and A1203 concentrations in olivine and clinopyroxene during crystallization. The mineralogic features in the high-alumina basalts that were discharged by all parasitic eruptions of Klyuchevskoi provide evidence of magnesian magma being emplaced from a deeper chamber into a shallow high-alumina chamber. The distribution of incoherent elements in the volcano's magnesian and aluminiferous rocks shows that they came from a single mantle source. The geochemical and mineralogic data are in good agreement with the results of geophysical surveys that concern the structure and properties of the lithosphere beneath Klyuchevskoi.